KINERJA KEUANGAN SESUDAH DAN SEBELUM SPIN OFF UNIT USAHA SYARIAH KE BANK UMUM SYARIAH - Kuncoro, Amin; Yulianto, Heru (EQUILIBRIUM, 2018)
This study aims to distinguish between conventional banks and Islamic banks before and after Spin Off. The population and samples are Islamic banks in 2011 - 2013 before spin off and 2013 - 2016 after the spin off totaling 5 banks. The design of this study uses descriptive analytics, with the results of the study there are differences in Islamic banks that do spin offs.